Pengenalan Sains di Taman Kanak-kanak - I Wayan Sutama (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2006)
Young children are natural scientists. They are curious, and interested in everything, always try to find out what will happen. As young scientists, young children use the processes of science and thing to make observation and inferences about they think in their world. They try to understand the nature of their world; they think and do at the same time. They classify and reach conclusions. They learn their world by playing. By the way, in early childhood education, the teacher must construct the environment, questioning and offer information, lead children to expand their scientific world into more conventional ways of thinking. The teacher and adult must help them to learn to know, to do, to be and to life together.